Analisis Pemanfaatan Dana Desa dalam Pembangunan Infrastruktur di Desa Tangeban Kecamatan Masama: Analysis of the Utilization of Village Funds in Infrastructure Development in Tangeban Village Masama District - Annisa Laise; Amir Buhang (Jurnal Ilmiah Produktif, 2020)
The problem formulation of this research is how to use village funds in infrastructure development in Tangeban Village, Masama District. This research uses a qualitative approach . Data collection techniques in this study were interviews and documentation. The results showed that the village development in Tangeban Village, namely the construction of concrete rebates, construction of retaining walls. In the context of this development, of course, the construction of concrete rebates provides good benefits for the people of Tangeban Village. In the development planning process there were 2 constructions of concrete rebates that were not realized properly, namely the construction of concrete rebates for RT 02 and concrete rebates for 46 m3 for RT 03. In each item of concrete rebate development that has been implemented, one of the construction of concrete rebates was made along a length of 28 m3 which is located in RT 01 it was not done well due to the uneven distribution of the land at the time of the work as a result it broke down so that the people of Tangeban village used boards as a path to pass the road, which of course did not provide benefits for the people of Tangeban village. It can be concluded that the use of the Village Fund for the implementation of village development does not provide significant benefits to the Tangeban village community.